Mechanism of zinc ejection by disulfiram in nonstructural protein 5A. Issue 21 (19th May 2021) - Rehman, Ashfaq Ur; Zhen, Guodong; Zhong, Bozitao; Ni, Duan; Li, Jiayi; Nasir, Abdul; Gabr, Moustafa T.; Rafiq, Humaira; Wadood, Abdul; Lu, Shaoyong; Zhang, Jian; Chen, Hai-Feng
Abstract : Hepatitis C virus (HCV) is a notorious member of the Flaviviridae family of enveloped, positive-strand RNA viruses. Abstract : Hepatitis C virus (HCV) is a notorious member of the Flaviviridae family of enveloped, positive-strand RNA viruses. Non-structural protein 5A (NS5A) plays a key role in HCV replication and assembly. NS5A is a multi-domain protein which includes an N-terminal amphipathic membrane anchoring alpha helix, a highly structured domain-1, and two intrinsically disordered domains 2–3. The highly structured domain-1 contains a zinc finger (Zf)-site, and binding of zinc stabilizes the overall structure, while ejection of this zinc from the Zf-site destabilizes the overall structure. Therefore, NS5A is an attractive target for anti-HCV therapy by disulfiram, through ejection of zinc from the Zf-site. However, the zinc ejection mechanism is poorly understood. To disclose this mechanism based on three different states, A-state (NS5A protein), B-state (NS5A + Zn), and C-state (NS5A + Zn + disulfiram), we have performed molecular dynamics (MD) simulation in tandem with DFT calculations in the current study. The MD results indicate that disulfiram triggers Zn ejection from the Zf-site predominantly through altering the overall conformation ensemble. On the other hand, the DFT assessment demonstrates that the Zn adopts a tetrahedral configuration at the Zf-site with four Cys residues, which indicates a stable protein structure morphology. Disulfiram binding induces major conformational changes at the Zf-site, introduces new interactions of Cys39 with disulfiram, and further weakens the interaction of this residue with Zn, causing ejection of zinc from the Zf-site. The proposed mechanism elucidates the therapeutic potential of disulfiram and offers theoretical guidance for the advancement of drug candidates.